Evaluation of hypoglycaemic and hypolipidemic activities of Globularin isolated from Globularia alypum L. in normal and streptozotocin-induced diabetic rats - Salima Merghache, Meriem Zerriouh, Djamila Merghache, Boufeldja Tabti, Rabah Djaziri, Saïd Ghalem (Journal of Applied Pharmaceutical Science, 2013)
The present study investigates the effect of intraperitoneal administration of Globularin on blood glucose levels in normal and streptozotocin diabetic rats. Globularin was an iridoid glucoside which was isolated from the leaves of Globularia alypum (3.4 %). This compound was identified by means of physical constants and spectral data UV, IR, MS, 1H-NMR, 13C-NMR, DEPT, COSY, HMBC. The acute toxicity test demonstrated that Globularin is not lethal up to dose of 1000 mg/kg body weight after intraperitoneal injection. In normal and streptozotocin diabetic rats, single intraperitoneal administration of Globularin at a dose 100 mg/kg body weight produced significant decrease of blood glucose levels. However, in prolonged treatment study, the repeated intraperitoneal administration of Globularin (2 x 100 mg/kg body weight) decreased significantly the blood glucose levels when compared to the diabetic control rats. In addition, daily injection of Globularin (2 x 100 mg/kg body weight) reduced significantly serum levels of total cholesterol (varied from 0.53 to 0.41 g/L) and triglycerides (varied from 1.71 to 0.79 g/L) in the diabetic rats.
Keywords: Globularia alypum L. (Globulariac